EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PAUD: ANALISIS KRITIS KURIKULUM MERDEKA UNTUK PENDIDIKAN MASA KINI - Nofrizal, Nofrizal; Faisal, Muhammad; Mitra, ⁠Fitria; Nofrizal, Edi; ⁠Julhadi, ⁠Julhadi (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
This study aims to evaluate the implementation of Islamic Religious Education (PAI) teaching in Early Childhood Education (PAUD) and analyze the relevance of the Merdeka Curriculum in its application. Using the Systematic Literature Review (SLR) method, this study examines the related literature to understand the evaluation approaches applied to PAI in PAUD, as well as the challenges and opportunities arising from the implementation of the Merdeka Curriculum. The findings reveal that the evaluation of PAI in PAUD is diverse, with formative and summative assessment approaches commonly used. However, there are gaps, particularly in teachers' understanding of the principles of the Merdeka Curriculum and the integration of appropriate learning materials. The Merdeka Curriculum offers flexibility and relevance, but its implementation is hindered by the lack of teacher training and the availability of adequate teaching materials. Based on these findings, the study recommends the development of clearer evaluation guidelines, enhanced teacher training, and increased collaboration between educators, PAUD institutions, and policymakers. With these steps, it is expected that PAI teaching will be more effective in shaping children's character with noble morals. Keywords: PAI Learning Evaluation; Merdeka Curriculum; PAUD; Islamic Religious Education; Systematic Literature Review (SLR).